Pemertahanan Bahasa Bali Dialek Nusa Penida sebagai Sumber Konten Kreatif: Kajian Sosiolinguistik Kanal YouTube Alit Werdi Suputra - Made Reland Udayana Tangkas; A. A. Pt. Suari (Universitas Udayana, 2023)
This research examines the maintenance of the Balinese Nusa Penida Dialect (DNP) on the growing popular YouTube channel Alit Werdi Suputra. The problems studied are the use of the DNP form and their social aspects. Data collected from selected content of Alit Werdi Suputra Youtube channel by note taking technique. Collected data were analysed by sociolinguistic theory by focusing on language maintenance. The study found that the use of DNP reflects the social life of the people of Nusa Penida and social aspects were found including culture, morality, love, education, and politics. The result of this research offers important inspiration for other content creators to raise and promote the Balinese language among YouTube audiences including the millennial generation. This research also has the benefit of seeing the significance of YouTube in maintaining local language, specifically through the introduction of local dialect into the young generation who are the active audience of social media.